Influence of TATO, DER and NPM on Profit Growth in Property and Real Estate Sub-Sector Companies Listed on the IDX - Indah Lestari; D. Damayanti; Nur Listiani (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the effect of Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) on profit growth. The objects of this study were property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Sampling was conducted using a purposive sampling technique, with a sample size of 22 property and real estate companies. Based on the statistical analysis, it can be concluded that TATO has a positive but insignificant effect on profit growth. Based on the statistical analysis, it can be concluded that DER has a positive but insignificant effect on profit growth. Based on the statistical analysis, it can be concluded that NPM has a positive but insignificant effect on profit growth. This indicates that increasing the efficiency of asset use, capital structure, and profitability levels have not been able to significantly influence profit growth. Thus, it can be concluded that TATO, DER, and NPM are not entirely the main factors in driving profit growth in property and real estate companies. This research is expected to be a consideration for company management and investors in decision-making and serve as a reference for further research.